ChemInform Abstract: Synthesis of P‐Stereogenic Phosphoramidite and Phosphorodiamidite Ligands and Their Application in Asymmetric Catalysis. Issue 7 (January 2016) - Schmitz, Christian; Leitner, Walter; Francio, Giancarlo
Abstract: A library of novel P‐stereogenic phosphoramidite and phosphorodiamidite ligands based on chiral Betti bases are synthesized (not shown) and applied to Rh‐catalyzed asymmetric hydrogenation as well as Pd‐catalyzed allylic amination and a Ni‐catalyzed hydrovinylation.